Pig the fibber - Blabey, Aaron (Blabey, Aaron. Pig the pug (Series), 2018)
Pig the Pug often lies to get what he wants, and blames Trevor the sausage dog for his own misdeeds--but when his latest lie results in an accident and the loss of a tooth he finally learns his lesson (maybe).